The Influence Self-esteem and Narcissism towards Instagram Addiction Among Emerging Adults - Rosanna Fadiya; Djoko Setyabudi; Nurist Surayya Ulfa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Instagram is one of the most popular social media platform in Indonesia. Compared to other SNSs, Instagram has the worst effects on young people's mental health. Those with poor self-esteem use Instagram as a tool for self-improvement (taking photos and videos and compare it with other users), while narcissistic people use it for satisfaction (create false image to appear more appealing). This study aims to explain the influence of self-esteem and narcissism towards Instagram addiction among emerging adults using I-PACE model, with non-probability sampling technique (snowball sampling). A total of 100 emerging adults aged 18-25 who actively use Instagram were recruited as respondents for this research. The results of the hypothesis tests using multilinear regression analysis technique shows that there is an influence of self-esteem and narcissism on Instagram addiction with a significant value of (0.000). This shows that both self-esteem and narcissism has an influence on respondents’ addiction to Instagram.